Sub-Antarctic Magellanic Ornithology : The First Decade of Bird Studies at Omora Ethnobotanical Park, Cape Horn Biosphere Reserve - Calcutta, Alejandra; Rozzi, Ricardo, 1960-; Jimenez, Jaime E., 1960- (Book collections on Project MUSE., 2014)
The first synthesis of current knowledge of forest and wetland birds in the world''s southernmost forests, this book contains both original work by Rozzi and Jimenez and the results of a decade of research conducted by the scientists associated with the Omora Park.